Grouping of Red Flour Beetles using two Different Strains - Henery, Caroline; Marshall, Jeremy (My University, 2018)
In this research project I studied how the Red Flour Beetle grouped over a 10 day time period with two different strains of the Beetle. One strain was the Canadian Red Flour Beetle and the other was the Manhattan, KS Red Flour Beetle. The grouping of the beetles is a behavior that is being tested in this experiment and can be greatly effected by both environment and genetics (Breed & Sanchez, 2010). Thus for this experiment I ask if different strains of the Red Flour Beetle aggregate differently and hypothesize that they will end up aggregating differently. After testing this question and hypothesis I found that The different strains do aggregate differently and this could be due to the different climates at which they are normally found. The Canadian lives in an overall lower temperature year round unlike the Kansas beetle (Baldwin & Fasulo, 2014). With this knowledge grain facilities will be able to better prevent infestations of this particular beetle (Gerken, Scully, &Campbell, 2018).
Keywords: Fall 2018